Effects of in-feed clinoptilolite treatment on serum metabolic and antioxidative biomarkers and acute phase response in dairy cows during pregnancy and early lactation. (December 2019) - Folnožić, Ivan; Samardžija, Marko; Đuričić, Dražen; Vince, Silvijo; Perkov, Sonja; Jelušić, Sanja; Valpotić, Hrvoje; Ljubić, Blanka Beer; Lojkić, Martina; Gračner, Damjan; Žaja, Ivona Žura; Maćešić, Nino; et al.
Abstract: The objective of this study was to evaluate the effects of in-feed clinoptilolite (CPL) on serum metabolic and antioxidative biomarkers, acute phase proteins and reproductive performance in cows during pregnancy and lactation. A total of 78 Holstein-Friesian cows were randomly assigned into two groups: the treatment group, cows fed CPL ( n  = 38) which received 50 g of powdered CPL twice a day from day 180 before parturition to day 60 postpartum; and the control group ( n  = 40). Blood samples were taken on days 180, 90, 60, 30 and 10 before parturition, on day of calving and on days 5, 12, 19, 26, 33, 40 and 60 postpartum, and were analysed for metabolic biomarkers: glucose, triglycerides, total cholesterol, high density lipoprotein cholesterol, non-esterified fatty acids, beta-hydroxybutyrate (BHB), antioxidative biomarkers and acute phase proteins: paraoxonase-1 (PON1), apolipoprotein A-I, haptoglobin (Hp) and serum amyloid A (SAA). CPL supplementation increased concentration of glucose and significantly decreased ( P  < .05) level of BHB during puerperium. The SAA concentration in CPL-fed cows was significantly decreased ( P  < .05) on days 33, 40 and 60 postpartum as well as Hp concentration on days 0 and 12 postpartum. The results of this study suggest that the CPL-fed cows may have improved metabolic status due to the tendency of greater glucose levels and decreased BHB values during early lactation. In addition, acute phase response was lower ( P  < .05) in CPL-fed cows. Such an outcome might be attributed to the effect of dietary CPL on intensity and severity of the negative energy balance and inflammatory response in dairy cows. Highlights: Dietary clinoptilolite improves metabolic status in dairy cows. Acute phase response was lower in clinoptilolite-in feed supplemented cows. Clinoptilolite supplementation could affect severity of the NEB in dairy cows. Dietary clinoptilolite improved reproductive performance in dairy cows. Clinoptilolite supplement had a positive influence on milk yield in dairy cows.